Blockchain-Powered Secure and Transparent Citizen Participation Framework: A Roadmap for Nepal’s Digital Governance and Policy Implementation - Timalsina, Johnson; Bhandari, Eliza (International Journal on Engineering Technology and Infrastructure Development, 2025)
In order to ensure trust, transparency, and citizen engagement, Nepal's digital government initiatives—like the Nagarik App and Hello Sarkar—face significant obstacles. This paper presents a blockchain-powered framework to improve safe and open citizen participation in Nepal's digital governance ecosystem in order to get over these restrictions. The system guarantees decentralized and impenetrable record-keeping at the federal, provincial, and local levels of government by utilizing permissioned blockchain networks. Secure authentication and privacy preservation are made possible by Self-Sovereign Identity (SSI), which gives residents total control over their digital identities. Smart contracts reduce the risk of corruption and bureaucratic inefficiencies by automating crucial governance processes including the management of land records, the delivery of subsidies, and the resolution of grievances. The framework includes a token-based incentive system that rewards citizens for participating in public feedback mechanisms, e-voting, and service validation in order to promote active civic involvement. Fraud detection, data-driven decision-making, and real-time policy optimization are made possible by combining AI with big data analytics. A path for phased implementation is suggested, starting with trial installations in smart cities in Gandaki Province and working its way up to the national level. Scalability, legal compliance with Nepal's Electronic Transactions Act (2008), and limitations in rural digital infrastructure are among the important issues the study tackles. In order to increase the effectiveness of policy implementation, maintain data integrity, and foster public trust, this study proposes a novel paradigm for digital governance in Nepal that blends blockchain, artificial intelligence, and citizen-centric incentives. The suggested framework is a scalable model for developing countries looking for governance systems that are open, inclusive, and impervious to corruption.